Bidding Evaluation and Contractor Selection Using Balance Index Model and Comprehensive Input Efficiency Based on Data Envelopment Analysis - Xun Liu; Siyu Chen; Zhenhan Ding; Bixiao Xu (Systems, 2023)
In order to ensure a smooth construction project, it is necessary to select an appropriate contractor. However, traditional bid evaluation methods are highly subjective in determining weights. Data envelopment analysis (DEA), a comprehensive bid evaluation method that considers multiple factors, was introduced to reduce subjectivity and provide a simple yet comprehensive method for evaluating bids. Based on the existing cross-evaluation and balance index models, this research proposed a new DEA ranking model—the comprehensive input efficiency model, as well as its specific application steps. Additionally, a case study on selecting contractors for a water engineering project was presented to demonstrate the effectiveness of this model. The results indicated that the comprehensive input efficiency model could achieve the same ranking function as the balance index and was suitable for assessing bidders’ relative efficiency. Moreover, the comprehensive input efficiency model proposed in this research is more simplified. Thus, this research compensates for the drawbacks of the existing comprehensive evaluation models in that the bid evaluation process is cumbersome, thereby extending the research on DEA methods in bid evaluation. Additionally, the model provides tenderers with a more efficient and effective bid evaluation method to select the most appropriate contractor. In the future, research may be conducted to apply DEA to other types of projects, including service projects, real estate, and consulting services.